Analisis Pengelolaan Kelas Pembelajaran PAI dan Budi Pekerti Berbasis Multimedia di SMK - Hanafi hanafi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to analyze the management of Islamic religious education and multimedia-based learning classes at the vocational high school level. This research was conducted because at this level there are sometimes many discrepancies between implementation and planning. The approach used is descriptive qualitative with the collection method consisting of observation, interviews, and documentation. Based on the results of the study obtained information that planning, implementation, evaluation, and students' perceptions of multimedia-based learning are in accordance with predetermined competency standards.